Penurunan Kecelakaan Kerja dengan Mempertimbangkan Human Error menggunakan Metode SHERPA dan HEART (Studi Kasus pada Perusahaan Packaging) - Ridwan Riyadi; Winarno Winarno (Fakultas Teknik, 2023)
Occupational safety and health is an important factor in the smooth running of production so that the program must be implemented in the company. Work accidents can occur due to unsafe working conditions or due to human error. The purpose of this research is to reduce work accidents by considering the human error that occurs in the company. To solve this problem, the SHERPA and HEART methods are used. The SHERPA method is used to predict errors and analyze potential solutions qualitatively, while the HEART method is used to calculate the probability level of a possibility of an error occurring in a structured manner. Based on the results of work accident data processing using the SHERPA method, it is known that 4 tasks have moderate probability ordinal analysis and 1 task has low probability ordinal analysis. Based on the HEART method, it is known that the largest human error probability with a value of 0.928 is located in task 1 and task 5. Proposed improvements to reduce work accidents by imposing penalties on workers who do not use personal protective equipment while working and providing socialization regarding the importance of work safety.